HEAT EXCHANGER NETWORK SYNTHESIS CONSIDERING CHANGING PHASE STREAMS - Liporace, F. S.; Pessoa, F. L. P.; Queiroz, E. M. (Revista de Engenharia Térmica, 2004)
The Pinch Design Method was developed considering one-phase streams, with constant specific heats (Cp) throughout streams temperature ranges. Its first stage, the determination of utilities targets and pinch point (PP), is ruled by the number of streams, their temperatures and MCp. But, for changing phase streams, the usual description of the Cp behavior by a constant value can lead to errors in this stage and, hence, in the synthesis one. This work proposes a procedure to deal with these streams and discusses its results through an example involving multicomponent streams. First, bubble (BP) and dew (DP) points of the streams are estimated. Then, changing phase streams are split into sub-streams, using BP and DP as bounds. For each one, an effective Cp is estimated as the division of the enthalpy change by the respective temperature difference. Results obtained show significant changes on the PP, utilities targets and network proposed structure.